Investigating the Utility of Birds in Precontact Yup’ik Subsistence: A Preliminary Analysis of the Avian Remains from Nunalleq - Masson-MacLean, Edouard; Houmard, Claire; Knecht, Rick; Moss, Madonna (Études Inuit Studies, 2019)
Birds have been an integral part of traditional Yup’ik lifeways in the Yukon–Kuskokwim Delta, southwest Alaska, both economically and symbolically. From a subsistence point of view, the rich ethnographic record for the region highlights the importance of this resource as a critical seasonal food and a source of raw materials for clothing and tools. Little is known of bird exploitation in precontact Yup’ik society, however, as a result of limited archaeological research in the region, which thus constrains our ability to understand subsistence strategies prior to Euro-American contact. Recent excavations at the Nunalleq site (sixteenth to seventeenth century AD) have yielded a well-preserved avian assemblage that provides the opportunity to explore the use of birds during the late prehistoric period in the region. In this paper, we present the results of our preliminary zooarchaeological and technological analyses of this material. These new data demonstrate that a relatively wide range of taxa were harvested by precontact Yupiit, reflecting their multiple uses of birds. People not only exploited birds for their meat but also targeted specific taxa for the qualities of their skins for making parkas, their feathers as adornments or for fletching arrows, and their bones for making needles and other tools. Though this study shows a certain degree of continuity between precontact and historic Yup’ik subsistence practices, it also highlights a gradual decline in the non-dietary use of birds and the gradual increase in the intake of birds primarily targeted as sources of food in more recent times.